Maternal-Fetal Attachment and Maternal Identity according to Type of Stress Coping Strategies on Immigration Pregnancy Women - Hyeun Na; So Hyun Moon (Korean Society of Women Health Nursing, 2015)
PURPOSE: The purpose of this descriptive survey study was designed to identify the stress coping types of married immigrant pregnant women and find out the differences in maternal-fetal attachment and maternal identity based on each types. METHODS: 151 married immigrant women who visited 3 women's hospitals located in J-do for pre-pregnancy checkup were selected as study objects. Data were analyzed by dsecriptive statistics, cluster analysis, t- test, ANOVA, and Scheffe multiple comparison test. RESULTS: Cluster analysis revealed 4 distinct stress coping styles; low stress-coping involvement social support-oriented type, high stress-coping involvement hopeful thinking type, low stress-coping involvement type, effective stress coping types. Women frequently using effective stress coping type among the four types reported higher maternal-fetal attachment. The group of active coping styles got significantly higher score on maternal identity. CONCLUSION: Proper stress coping of married immigrant pregnant women regarding pregnancies proved to result in high levels of maternal-fetal attachment and maternal identity. Studies measuring the stress coping styles that affect pregnancies should be continuously conducted.